Recent findings and future directions for interpolar mitotic kinesin inhibitors in cancer therapy. (March 2016) - Myers, Stephanie M; Collins, Ian
The kinesin class of microtubule-associated motor proteins present attractive anticancer targets owing to their roles in key functions in dividing cells. Two interpolar mitotic kinesins Eg5 and HSET have opposing motor functions in mitotic spindle assembly with respect to microtubule movement, but both offer opportunities to develop cancer selective therapeutic agents. Here, we summarize the progress to date in developing inhibitors of Eg5 and HSET, with an emphasis on structural biology insights into the binding modes of allosteric inhibitors, compound selectivity and mechanisms of action of different chemical scaffolds. We discuss translation of preclinical studies to clinical experience with Eg5 inhibitors, recent findings on potential resistance mechanisms and explore the implications for future anticancer drug development against these targets.